A stratified method of formalization of multistate complex technological systems - Seyran Shamirovich Balasanyan (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the discussed issue is caused by the need to develop a problem-oriented method of hierarchical multilevel (stratified) formalization which allows to overcome the difficulties of modeling multistate complex technological systems in studying the efficiency of their functioning, taking into account the impact of elements reliability. The main aim of the study: development of a problem-oriented stratified method of formalization of complex technological systems of a certain class with a large dimension of state space and its practical application in the development of a stratified model of technological system of ore grinding, with due consideration of the impact of equipment reliability on its functioning efficiency. The methods used in the study: concept of multilevel hierarchical description of complex systems, general theory of systems, theory of reliability, simulation method, algebra of logic, methods of applied statistics. The results. The authors proposed a problem-oriented method of stratified formalization which allows to overcome the difficulties of formalizing CTS of a certain class in the study of efficiency of their functioning taking into account the reliability of components by simulation modeling. By using the proposed method the authors developed a stratified computer model of ore grinding of Zangezur Copper Molybdenum Combine (Armenia), describing the process of its functioning under the influence of the random process of failures and recovery of failed equipment at three levels: at the level of grinding aggregates, at the level of grinding complexes and at the system level. Application of the proposed method of formalizing allowed to reduce the description of ore grinding technological system to the description of its parts and their conjugation, giving the possibility of analytical description of the system at the first and third levels. Thanks to this the construction of a simulation model of the overall system can be substantially simplified, the number of full-scale experiments is drastically reduced, which, in turn, has led to a significant reduction in time and complexity of building a computer model of the whole system.